Cysteine allows ovarian cancer cells to adapt to hypoxia and to escape from carboplatin cytotoxicity - Nunes, Sofia C. (2018)
The authors would like to acknowledge the Instituto Portugues de Oncologia de Lisboa Francisco Gentil (IPOLFG) for partially funding the project. We would also like to acknowledge Dr Dialina Brilhante and Dr. Teresa Guerreiro (Servico de Imuno-hemoterapia, IPOLFG) for providing blood donors samples; to Dr Humberto Goncalves (Pharmacy, IPOLFG) for paclitaxel and carboplatin preparation, and Marta Teixeira (IBET) for the technical support in 3D models. The study was also funded by Projecto TVI. This research was supported by Fundacao para a Ciencia e Tecnologia (FCT) (PhD ProRegeM program, PD/BD/105893/2014, FCT fellowship, PD/BD/105768/2014). iNOVA4Health - UID/Multi/04462/2013, a program financially supported by Fundacao para a Ciencia e Tecnologia/Ministerio da Educacao e Ciencia, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement is acknowledged.